1996
DOI: 10.1016/0301-2115(96)02382-2
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the management of third stage of labour in the Netherlands

Abstract: The standard practice during the third stage of labour of Dutch midwives and obstetricians was elucidated by a questionnaire mailed to all Dutch midwives and obstetricians. Prophylactic oxytocics in the third stage are used as a routine by 55% of the obstetricians and only 10% of the midwives. Oxytocin is the drug of first choice. Conclusion; Routine use of prophylactic oxytocics in the third stage is not the standard practice in the Netherlands. Obstetricians are much more likely to use prophylaxis than mid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The choice of approach for third‐stage management may be influenced by facility, region of the country or world, and/or philosophy. In 1996, deGroot and colleagues (12) reported that, in the Netherlands, 55% of the obstetricians routinely administered a uterotonin prophylactically, a common active management technique; yet, only 10% of Dutch midwives were found to do so.…”
Section: Active Versus Expectant Managementmentioning
confidence: 99%
“…The choice of approach for third‐stage management may be influenced by facility, region of the country or world, and/or philosophy. In 1996, deGroot and colleagues (12) reported that, in the Netherlands, 55% of the obstetricians routinely administered a uterotonin prophylactically, a common active management technique; yet, only 10% of Dutch midwives were found to do so.…”
Section: Active Versus Expectant Managementmentioning
confidence: 99%
“…The limited scientific evidence for individual components of AMTSL and differences in philosophy of care have resulted in intrapartum care provider practice variations outside of the United States. International surveys of providers, primarily in developed countries, demonstrate the wide variation of AMTSL implementation . A study in British Columbia, Canada compared the preferred methods of family physicians, obstetricians, and midwives for managing the third stage of labor .…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study of experienced Swedish midwives revealed a reluctance to administer prophylactic medication . Significant practice variation was also found among providers in Australia and the Netherlands . A pilot observational, cross‐sectional study of 15 university–based referral obstetric centers participating in the Global Network for Perinatal and Reproductive Health found significant intracountry and intercountry variation in the practice of AMTSL .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, in Canada, no study has been previously published comparing different maternity care practitioners to determine their third-stage labor practice patterns. A study in the Netherlands showed a significant difference between obstetricians and midwives in their use of routine prophylactic oxytocin in managing the third stage of labor (55% vs 10%, respectively) (18).…”
mentioning
confidence: 99%